2018
DOI: 10.5194/angeo-36-1495-2018
|View full text |Cite
|
Sign up to set email alerts
|

Case study of ozone anomalies over northern Russia in the 2015/2016 winter: measurements and numerical modelling

Abstract: Abstract. Episodes of extremely low ozone columns were observed over the territory of Russia in the Arctic winter of 2015/2016 and the beginning of spring 2016. We compare total ozone columns (TOCs) from different remote sensing techniques (satellite and ground-based observations) with results of numerical modelling over the territory of the Urals and Siberia for this period. We demonstrate that the provided monitoring systems (including the new Russian Infrared Fourier Spectrometer IKFS-2) and modern three-di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Nevertheless, in January-February 2016, lower values of the total column ozone (up to ~200 Dobson Units (DU)) were observed in the northern part of Russia, which was 50% less than the average climatic values [20]. Analysis of the model simulation revealed that these anomalies were mainly due to Dynamic reasons [21].…”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, in January-February 2016, lower values of the total column ozone (up to ~200 Dobson Units (DU)) were observed in the northern part of Russia, which was 50% less than the average climatic values [20]. Analysis of the model simulation revealed that these anomalies were mainly due to Dynamic reasons [21].…”
Section: Introductionmentioning
confidence: 94%
“…Nowadays, there are many chemistry-transport models (CTMs) and chemistry-climate models (CCMs) which differ in coverage of the Earth (global and regional), spatial and temporal resolution, considered physical and chemical processes and other characteristics. Series of studies have demonstrated successful implementation of the models for investigating the atmospheric ozone content variations, determination of main factors influencing stratospheric ozone and estimation of the future and past of the ozonosphere [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%